SELECTION OF KRI HARDEPO PRIORITIES USING THE FUZZY MCDM METHODS - Bambang Suharjo; I Made Jiwa Astika; Agus Setiadji; Joko Purnomo (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2020)
The Unitary State of the Republic of Indonesia (NKRI) is the largest archipelagic country in the world, two thirds of which are is seas, requiring the presence of the KRI in maintaining its sovereignty. Continuity of attendance in carrying out its main duties, the Navy depends on the readiness of the KRI (Indonesian Republic Warship). The Navy's strength development program is bound to the MEF (Minimum Essencial Force), the basic development policy of TNI AL towards minimum principal strength. The main target of MEF is a limited amount but can operate optimally. So we need a program to overcome these problems by maximizing the defense system maintenance program called SPT (Planned Maintenance System). To maximize the planned maintenance system that supports the MEF program requires prioritization in selecting the KRI that will carry out Depo level improvement (Hardepo). The selection of KRI determination that will implement Hardepo has several factors that need to be considered so that it is categorized in a multi-criteria decision environment, then the proposed model becomes an appropriate methodology to accommodate the criteria with the Fuzzy MCDM (Multi Criteria Decision Maker) approach. In this study there are six alternative KRI namely KRI Keris-624, KRI Rimau Island-726, KRI Kerapu-812, KRI Badau-841, KRI Jakarta Bay-541 and KRI Arun-903 where the first priorities obtained are KRI Rimau Island- 726 with a weight value of 0.1778. After the priority is obtained then schedule the duration and availability of Docking at PT PAL Indonesia where all KRI can carry out docking every TW (Tri Wulan) except KRI Arun-903 which cannot carry out docking on TW I 2019. Keyword : MEF, SPT, Hardepo, Fuzzy MCDM, Docking Scheduling.